Effect of weed management on growth, yield and economics of dill (Anethum graveolens L.) in typic haplustept soils - Ruchika Choudhary; Arvind Verma; H. K. Sumeria; Manish Tomar; Kannoj (Scientific Reports)
Abstract Weed management is a critical factor influencing returns yield and economic returns of dill (Anethum graveolens L.). A field experiment was conducted during the rabi seasons of 2020–2021 and 2021–2022 at MPUA&T, Udaipur, Rajasthan, to evaluate the efficacy of various weed control strategies in dill cultivation. The study, laid out in a randomized block design with three replications, comprised thirteen weed control treatments, including pre and post emergence herbicides and integrated approaches. The application of oxadiargyl at 75 g/ha as a pre-emergence herbicide, followed by hand weeding at 40 days after sowing (DAS), resulted in the highest weed control efficiency (96.42% at 60 DAS) and significantly reduced weed density and biomass. This treatment improved growth attributes such as plant height, dry matter accumulation, and branches per plant, leading to a 61.58% increase in seed yield (7.66 q/ha) compared to the weedy check (4.74 q/ha). Economic analysis revealed that this integrated approach provided the highest net return (USD 770.59/ha) and benefit-cost ratio (1.93), making it the most effective and profitable weed management strategy for dill cultivation.